Membrane binding, internalization, and sorting of alpha-synuclein in the cell - Masaracchia, Caterina (2018)
Alpha-synuclein (aSyn) plays a crucial role in Parkinson's disease (PD) and other synucleinopathies, since it misfolds and accumulates in typical proteinaceous inclusions. While the function of aSyn is thought to be related to vesicle binding and trafficking, the precise molecular mechanisms linking aSyn with synucleinopathies are still obscure. aSyn can spread in a prion-like manner between interconnected neurons, contributing to the propagation of the pathology and to the progressive nature of synucleinopathies. Here, we investigated the interaction of aSyn with membranes and trafficking machinery pathways using cellular models of PD that are amenable to detailed molecular analyses. We found that different species of aSyn can enter cells and form high molecular weight species, and that membrane binding properties are important for the internalization of aSyn. Once internalized, aSyn accumulates in intracellular inclusions. Interestingly, we found that internalization is blocked in the presence of dynamin inhibitors (blocked membrane scission), suggesting the involvement of the endocytic pathway in the internalization of aSyn. By screening a pool of small Rab-GTPase proteins (Rabs) which regulate membrane trafficking, we found that internalized aSyn partially colocalized with Rab5A and Rab7. Initially, aSyn accumulated in Rab4A-labelled vesicles and, at later stages, it reached the autophagy-lysosomal pathway (ALP) where it gets degraded. In total, our study emphasizes the importance of membrane binding, not only as part of the normal function but also as an important step in the internalization and subsequent accumulation of aSyn. Importantly, we identified a fundamental role for Rab proteins in the modulation of aSyn processing, clearance and spreading, suggesting that targeting Rab proteins may hold important therapeutic value in PD and other synucleinopathies.